ECONOMIC VALUATION OF MANGROVES FOREST RESOURCES IN REGENCY OF BANGGAI DAN BANGGAI ISLAND CENTRAL SULAWESI - Sugeng Putranto; Neviaty P. Zamani; Harpasis S. Sanusi; Etty Riani; Achmad Fahrudin (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2017)
This study aims to determine how big the value of the total economic benefits of mangrove forest by using the concept of economic valuation to calculate the value of the benefits of natural resources which exist in 9 District of Banggai Regency and Banggai Island Regency located in Peleng Strait Costal Area there are: District of Batui Selatan, Batui, Luwuk Timur, Lamala, Masama, Balantak, Bualemo (in Banggai Regency Area) and District of Buko and Buko Selatan (Banggai Island Regency). The research was conducted in August to November 2016, by conducting field observations and interviews directly to the community and local government. Based on the results obtained that indicate the area of mangrove forest ecosystems in Peleng Strait Costal Area with a broad ± 167 ha, have total value of economic benefits amounted Rp 26,591,841,888/year with the largest contributor to the value of benefits is from the value of indirect benefits that is the value of the benefits of mangrove forests as a buffer abrasion or sea water waves is about Rp 16.030.000.000. The total value of economic benefits can be used as a reference or basic comparison for the community and the government in determining the policy management and utilization of existing mangrove forests. Keywords: mangrove forest ecosystems, benefits value, economicvaluation